Türkmen Türkçesinde cümle ve cümlecik biçimlerindeki deyimler - Seyhun, Cennet (My University, 2019)
ÖZETSEYHUN ÖZTÜRK, Cennet, Türkmen Türkçesinde Cümle ve Cümlecik Biçimlerindeki Deyimler, stanbul, 2019.Deyimler, anlatıma akıcılık ve çekicilik katan, genellikle gerçek anlamının dışında kullanılan, toplumun benimsediği kalıplaşmış söz öbekleridir. Deyimler birden çok yapısal özellik gösterirler. Bazı deyimler, cümle ve cümlecik yapılarında kalıplaşmışlardır.Bu çalışmada Türkmen Türkçesindeki cümle ve cümlecik biçimlerindeki deyimler derlenerek incelenmiştir. Derleme aşamasında; 2015 yılında Türkmenistan İlimler Akademisi Mahtumkulı Dil ve Edebiyat Enstitüsü’nün yayımladığı “Türkmen Diliniň Düşündirişli Sözlügi”, 2013 yılında yayımlanan “Türkmen Diliniň Frazeologik Sözlügi”, Mehmet Kara ve Ahmet Karadoğan’ın “Türkmen Türkçesi-Türkiye Türkçesi Deyimler Sözlüğü” kaynak olarak kullanılmıştır.İnceleme kısmında metindeki cümle biçimindeki deyimler cümle türleri bakımından incelenmiş, cümlecik biçimindeki deyimler ise isim-fiil, sıfat-fiil ve zarf-fiil başlıkları altında incelenmiştir.Metinde, derlenen deyimler Türkmen Latin alfabesiyle yazılıp Türkmen Türkçesi konuşma diline uygun olarak transkripsiyonu yapılmıştır. Deyimlerin anlamları da açıklanarak Türkiye Türkçesindeki eş değerleri karşılarına yazılmıştır. Son olarak dizin kısmında deyimleri oluşturan kurucu sözcükler ve birleşik sözcüklerin dizini yapılmıştır.

ABSTRACTSEYHUN ÖZTÜRK, Cennet, Idioms in Sentence and Clause Forms in Turkmen Turkish, Master’s Thesis, İstanbul, 2019.Idioms are stereotypes that are adopted by the society, which are generally used out of their real meaning, adding fluency and charm to the narrative. Idioms show multiple structural features. Some idioms are stereotyped in sentence and clause structures.In this study, idioms in sentence and clause forms in Turkmen Turkish have been compiled and examined.During the compilation stage, “Türkmen Diliniň Düşündirişli Sözligi” which was published in 2015 by the Academy of Turkmenistan Sciences Mahtumkulu Language and Literature Institute, also “Türkmen Diliniň Frazeologik Sözlügi” which was published in 2013 and from Mehmet Kara and Ahmet Karadoğan Türkmen Türkçesi-Türkiye Türkçesi Deyimler Sözlüğü” have been used as source.In the examination part, the idioms in the form of sentences in the text, are examined in terms of sentence types and the idioms in the form of clauses, are examined under the titles of noun-verb, adjective-verb and adverb-verb.In the text, the compiled idioms were written in Turkmen Latin alphabet and transcribed in accordance with the Turkmen Turkish language. Equivalents in Turkey Turkish of idioms have been written by explaining meanings as well.Finally, in the index section, the constituent words and compound words that form the idioms are indexed.
Keywords: clause; cümle; cümlecik; deyimler; sentence; transkripsiyon idioms; transkription; Turkish literature; Turkmen language; Turkmen Turkish; Türk edebiyatı; Türkmen dili; Türkmen Türkçesi